Unveiling the spin evolution in van der Waals antiferromagnets via magneto-exciton effects - Wang, Xingzhi; Tan, Qishuo; Li, Tie; Lu, Zhengguang; Cao, Jun; Ge, Yanan; Zhao, Lili; Tang, Jing; Kitadai, Hikari; Guo, Mingda; Li, Yun-Mei; Xu, Weigao; et al. (Nature communications, 2024)
Among the fascinating phenomena observed in two-dimensional (2D) magnets, the magneto-exciton effect stands out as a pivotal link between optics and magnetism. Although the excitonic effect has been revealed and exhibits a considerable correlation with the spin structures in certain 2D magnets, the underlying mechanism of the magneto-exciton effect remains underexplored, especially under high magnetic fields. Here we perform a systematic investigation of the spin-exciton coupling in 2D antiferromagnetic NiPS 3 under high magnetic fields. When an in-plane magnetic field is applied, the exceptional sharp excitonic emission at ~1.4756 eV exhibits a Zeeman-like splitting with g ≈ 2.0, experimentally identifying the exciton as an excitation of dominant triplet-singlet character. By examining the polarization of excitonic emission and simulating the spin evolution, we further verify the correlation between excitonic emission and Néel vector in NiPS 3 . Our work elucidates the mechanism behind the spin-exciton coupling in NiPS 3 and establishes a strategy for optically probing the spin evolutions in 2D magnets. NiPS 3 , a van der Waals antiferromagnet exhibits exciton emission with a very sharp linewidth. The exact origin of this is has been a subject of active debate. Here, Wang et al study the behavior of this sharp exciton peak under applied magnetic fields, and find a Zeeman-like splitting, indicating the exciton has triplet-singlet character.